DESCRIPTION OF BODY IMAGE AMONG TEENAGERS - Nur Oktavia Hidayati; Hamidah Nurhalimah; Iwan Suhendar; Ikeu Nurhidayah (Journal of Maternity Care and Reproductive Health, 2021)
Body image has a big influence on teenagers in seeing themselves positively or negatively. A teenager sees him/herself positively, then he/she will have satisfaction with the body shape they have, so that his/her self-confidence increases. Meanwhile, if they judge themselves negatively there will be dissatisfaction with their body shape, which has an impact on decreasing his/her self-confidence. The purpose of this research was to determine the description of body image in teenagers at SMAN 17 Garut. This research was a descriptive research with quantitative approach. The population in this research were 606 teenagers who were students at SMAN 17 Garut. The sample of the research was 241 teenagers by taking stratified random sampling. Data collection techniques with body image instrument modified by Andiyati from the questionnaire (MBRSQ-AS). The results showed that 125 people (51.9%) were in the negative category and 116 people (48.1%) were in the positive category which meant this research showed that the body image of teenagers at SMAN 17 Garut were in the negative category and the results on aspects of respondent's body image was in the negative category. Based on the results of the research conducted at SMAN 17 Garut, to anticipate the emergence of body image in teenagers can be done by providing direction or motivation to prevent the occurrence of higher body image disorders among teenagers. This can be done through cooperation between teachers and nurses.